The entitlement effect in the ultimatum game: Does it even exist? - Elif E. Demiral; Johanna Mollerstrom (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Since the seminal paper of Hoffman et al. (1994), an entitlement effect is believed to exist in the Ultimatum Game, in the sense that proposers who have earned their role (as opposed to having it randomly allocated) offer a smaller share of the pie to their matched responder. The entitlement effect is at the core of experimental Public Choice - not just because it concerns the topics of bargaining and negotiations, but also because it relates to the question about under which circumstances actors behave more rational. We conduct three experiments, two in the laboratory and one online, with more than 1,250 participants. Our original motivation was to study gender differences, but ultimately we could not replicate the entitlement effect in the Ultimatum Game in any of our three experiments. Potential reasons for why the replication attempts fail are discussed.
Additional information: Corrected version of DP 1708 (2017).
Keywords: C7; C9; D72; J16; 330; Ultimatum Game; Public Choice; Experiment; Entitlement; Negotiations; Bargaining; Replications; Gender